Evaluation of ecological green high-quality development based on network hierarchy model for the demonstration area in Yangtze River Delta in China - Wang, Wen; Chen, Lihong; Yan, Xinfeng (Frontiers in Public Health, 2023)
The construction of the Yangtze River Delta ecological green development demonstration area aims to take the lead in exploring an eco-friendly development model, demonstrating and leading the higher quality integrated development of the Yangtze River Delta in China. Through literature research, expert inquiries, and policy documents as the guidance, this study builds an ecological green high-quality development evaluation system for the demonstration area, including building an index system composed of 4 first-class indicators, 16 second-class indicators and 42 third-class indicators derived from economy, society and environment system, determining the index weight through the network analytic hierarchy process, and establishing the comprehensive evaluation index (CEI) and differential diagnosis index (DDI) of high-quality development, which is based on the relevant theory of statistical comprehensive index. The establishment of this system provides a complete theoretical support and scientific guidance for the comprehensive evaluation of high-quality ecological green development and more balanced development of the demonstration area; and it can point out the development direction for the subsequent development of the Yangtze River Delta. However, due to the availability of data, there is still room for further improvement in this paper. In the future research, the model can be used to evaluate the high-quality development level of the demonstration area through the relevant data of the demonstration area.